17. Univocal IONM code. Issue 12 (December 2017) - Motti, L.; Torre, G.; Barsotti, M.; Ferrari, F.; Basile, C.
Abstract : By a verification of the IOMN activity throughout the whole Emilia Romagna territory, we have highlighted that almost all the hospitals level out on the methodology and materials, and as common critical point they all have the codification of the IONM intervention as a sum of health service codes of all the outpatient exams undertaken during the surgery in the operating room. Our hospital in 2014 has undertaken a path of cooperation with neurophysiology, the administrative sector and the neurosurgical staff, to create only 1 service code for the IONM activity, and obtain the code for this in a univocal code that realizes the effective activity that takes place in the operating room. By dividing the IONM activity in 3 main categories (spinal, subtentorial, supratentorial), we have undertaken a study that evidences the direct costs- staff costs, costs of the consumables and cost of the equipment- and indirect costs, posing the main attention on the variables depending on the operator, that can be modified to affect the total cost of the service, and on the variables unconnected and non-modifiable that are by default in the cost of the IONM. The finished price of the service was the result of the average of the total costs obtained in the completed calculation tables, completed and studied, obtaining a real cost of the service, inserting it in the list of the health service codes of the hospital. This achievement aims to be a model for all the realities on the territory, posing the first step for a standardization of the IONM.